2014
DOI: 10.3389/fpsyt.2014.00049
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Midline Activation during Symptom Provocation in Acute Stress Disorder: An fMRI Study

Abstract: Functional imaging studies of patients with post-traumatic stress disorder showed wide-spread activation of midline cortical areas during symptom provocation, i.e., exposure to trauma-related cues. The present study aimed at investigating neural activation during exposure to trauma-related pictures in patients with acute stress disorder (ASD) shortly after the traumatic event. Nineteen ASD patients and 19 healthy control participants were presented with individualized pictures of the traumatic event and emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
1
6
0
Order By: Relevance
“…However, depression in PTSD is present in approximately 66% and can be considered to emerge simultaneously as to two facets of a general posttraumatic psychopathology, 50,51 and our results can be generalized to a large clinically relevant population with PTSD. Although similar neural activation patterns have previously been found in acute and chronic PTSD during both symptoms provocation 5254 and picture viewing, 55 that PTSD symptoms had been present for 14 years on average limits the results to chronic PTSD. Since we used interpreters, there is a risk of miscommunication though it was not the impression that this has resulted in any clinically relevant information being lost.…”
Section: Discussionsupporting
confidence: 62%
“…However, depression in PTSD is present in approximately 66% and can be considered to emerge simultaneously as to two facets of a general posttraumatic psychopathology, 50,51 and our results can be generalized to a large clinically relevant population with PTSD. Although similar neural activation patterns have previously been found in acute and chronic PTSD during both symptoms provocation 5254 and picture viewing, 55 that PTSD symptoms had been present for 14 years on average limits the results to chronic PTSD. Since we used interpreters, there is a risk of miscommunication though it was not the impression that this has resulted in any clinically relevant information being lost.…”
Section: Discussionsupporting
confidence: 62%
“…Recent reports suggest that trauma exposure can trigger rapid brain changes within days of the event [ 15 21 ]. From two days to one month after trauma, activation to trauma-related stimuli is greater in PFC and right IC, but less in amygdala and hippocampus of trauma survivors compared to non-trauma exposed controls [ 17 19 ]. Traumatic experiences acutely alter functional coupling between amygdala and IC or hippocampus during processing of trauma-related stimuli [ 17 ] and between frontal-limbic-striatal and default mode network regions during rest [ 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the so-called alien limb syndrome which represents a violation of the sense of body integrity has been related to damage of the parietal cortex ( Graff-Radford et al, 2013 ) and the medial frontal cortex ( Feinberg et al, 1992 ; Biran et al, 2006 ) the latter of which was also related to an abolished self-reference ( Philippi et al, 2012 ). Evidence from functional imaging studies has revealed that the medial fronto-parietal circuit is critically abnormal in post-traumatic distress disorder reflecting altered mental functioning secondarily to a profound violation of the sense of safety ( Cwik et al, 2014 ). In fact, important aspects of believing, such as personal reference, empathy, and adequate control of behavior, appear to rely on the integrity of the medial and lateral prefrontal cortex.…”
Section: Neurophysiological Foundation Of Processes Of Believing and mentioning
confidence: 99%